Evaluation Of The Effect Of COMT Gene Polymorphism In Rs4680 On The Occurrence Of Concomitant Head, Neck And Back Pain In Patients With Temporomandibular Joint Disorders - Shamsoulmolouk Najafi; Hasan Roudgari; Nafise Sheykhbahaei; Amir Mohammad Oloumi (Journal of Craniomaxillofacial Research, 2024)
Background:  Temporomandibular disorders (TMD) include a number of clinical conditions involving the masticatory muscles, temporomandibular joint (TMJ), and adjacent structures. The main feature of TMD is pain. According to past studies, TMD can have genetic causes. One of the genes that seems to be important in this regard is COMT. This study aims to compare the effect of COMT gene polymorphism rs4680 on the occurrence of simultaneous head, neck and back pain in patients with TMD. Methods: This study was conducted as a case-control study on patients aged between 18 and 65 years who had TMD disorder. After meeting the conditions for entering the study, a written informed consent was obtained from the people participating in this project. Then a blood sample of 5cc was prepared from each person and poured into tubes containing EDTA anticoagulant and used for DNA extraction and identification. The COMT gene was sent to the genetics laboratory and was compared in terms of the polymorphism of the COMT gene using the PCRARMS technique. Results:  The sample size was 100 people aged 18 to 65 years. Variables with normal distribution were analyzed with Chi-Square test and variables with non-normal distribution with Mann-Whitney test. After genetic analysis in terms of rs4680 gene polymorphism, 18 people (18%) were identified with AA, 80 people (80%) with GA and 2 people (2%) with GG. "temporal headache in the last 30 days", "temporal headache change with chewing hard foods", "temporal headache change with opening the mouth or moving the jaw forward or to the sides", " Temporal headache changes with jaw habits such as teeth touching, pressing or grinding teeth together, chewing gum ", " Temporal headache changes with jaw activities such as talking, kissing or yawning ", " having Back pain during the last 4 weeks", having  pain in the arm, leg, joints (neck) during the last 4 weeks", “headache during 4 last weeks” and "time of onset of headache in the temporal region" did not have significant relationships with COMT gene polymorphism rs4680 in patients with TMD.(repectively, p value=0.873، p value=0.658، p value=0.518  p value=0.685،  p value=0.884،p value=0.654،  p value=0.723، p value=0.831، p value=0.692 ). Conclusion:  According to previous studies, there is a significant relationship between rs4680 polymorphism in the COMT gene and the occurrence of temporomandibular disorders (TMD), although in our study, no significant relationship was found between headache and neck and back pain with this polymorphism.